THE INFLUENCE OF ONLINE GUEST REVIEWS AND BRAND IMAGE ON THE TRIPADVISOR PLATFORM ON GUESTS' DECISIONS TO STAY AT THE TRANS RESORT BALI - Ni Komang Ayu Diah Arpany Jingga; Nyoman Indah Kusuma Dewi; Lily Marheni (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This study aims to analyze the influence of Online Guest Reviews and Brand Image on the Tripadvisor platform on guests' Stay Decisions at The Trans Resort Bali. This research employed a quantitative approach using a purposive sampling technique involving 100 respondents who had read reviews on Tripadvisor and stayed at The Trans Resort Bali. Data were collected through a questionnaire and analyzed using multiple linear regression with IBM SPSS Statistics version 27. The results indicate that, partially, Online Guest Reviews do not have a significant effect on Stay Decisions, with a significance value of 0.062 (>0.05). In contrast, Brand Image has a positive and significant effect on Stay Decisions, with a significance value of <0.001 (<0.05). Simultaneously, Online Guest Reviews and Brand Image have a significant effect on Stay Decisions, with a significance value of <0.001 (<0.05). The Adjusted R Square value of 0.209 indicates that these two variables explain 20.9% of the variance in Stay Decisions, while the remaining 79.1% is explained by other factors beyond the scope of this study. This study recommends that The Trans Resort Bali continue strengthening its Brand Image while optimizing the management of Online Guest Reviews as part of its marketing strategy. Keywords: Online Guest Review, Brand Image, Stay Decision.